Alternative roles for oxidized mCs and TETs. (February 2017) - Cimmino, Luisa; Aifantis, Iannis
Abstract : Ten-eleven-translocation (TET) proteins oxidize 5-methylcytosine (5mC) to form stable or transient modifications (oxi-mCs) in the mammalian genome. Genome-wide mapping and protein interaction studies have shown that 5mC and oxi-mCs have unique distribution patterns and alternative roles in gene expression. In addition, oxi-mCs may interact with specific chromatin regulators, transcription factors and DNA repair proteins to maintain genomic integrity or alter DNA replication and transcriptional elongation rates. In this review we will discuss recent advances in our understanding of how TETs and 5hmC exert their epigenetic function as tumor suppressors by playing alternative roles in transcriptional regulation and genomic stability.